KETAHANAN PANGAN RUMAH TANGGA PETANI KELAPA SAWIT DI KECAMATAN BANGUNREJO KABUPATEN LAMPUNG TENGAH - Alfu Mifta Khusufa; Dwi Haryono; fembriarti Erry Prasmatiwi (Lampung University, 2021)
The aims of this research are to analyze the level of food security, the factors that influence the level of household food security, and efforts to increase the level of food security of palm oil farmer households. The location of this research is chosen purposively in Bangunrejo Sub district, Central Lampung Regency in which respondents are 75 palm oil farmers household. The data were collected in January – March 2019 using a survey method and analyzed using cross-classification between the share of food expenditure and energy adequacy level, ordinal logistic regression, and descriptive qualitative analysis. The results of the research showed that the majority of farmer households (61.33%) were classified as food secure, and the rest were classified as less food secure (28%), vulnerable to food (9.33%), and food insecure (1.33%). The affecting factors on the level of food security were formal education level of housewives, households’ income, and number of household members. The efforts to increase the level of food security by Government were through monitoring food availability and food reserves, developing food distribution and stabilization of food prices, Program Keluarga Harapan (PKH), Raskin, and Bantuan Pangan Non Tunai (BPNT). Whereas, the efforts by palm oil farmer households were food loan (93.33%) and changing dietary habit (6.67%).Key words: cross-clasification, food security, palm oil farmer households